2021
DOI: 10.3390/cells10112960
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Control of Myeloid Cells in the Tumor Microenvironment

Abstract: Myeloid cells are a key determinant of tumor progression and patient outcomes in a range of cancers and are therefore being actively pursued as targets of new immunotherapies. The recent use of high-dimensional single-cell approaches, e.g., mass cytometry and single-cell RNA-sequencing (scRNA-seq) has reinforced the predominance of myeloid cells in the tumor microenvironment and uncovered their phenotypic diversity in different cancers. The cancerous metabolic environment has emerged as a critical modulator of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…The various states of polarization, activation and regulation of myeloid cells are accompanied by adaptation of lipid metabolism [ 14 , 15 ]. In contract, lipid metabolism modulates the activity of these cells [ 16 ].…”
Section: Lipid Metabolism In Myeloid Cellsmentioning
confidence: 99%
“…The various states of polarization, activation and regulation of myeloid cells are accompanied by adaptation of lipid metabolism [ 14 , 15 ]. In contract, lipid metabolism modulates the activity of these cells [ 16 ].…”
Section: Lipid Metabolism In Myeloid Cellsmentioning
confidence: 99%
“…Immune cells need to adapt to the challenges imposed by the TME, such as insufficient nutrients and oxygen. These conditions eventually impact their survival and functionality and are often linked to the acquisition of pro-tumorigenic properties (Strauss et al, 2021 ; Ramel et al, 2021 ). For instance, positron emission tomography imaging has shown that myeloid cells in tumors consume high amounts of glucose (Reinfeld et al, 2021 ), and our previous research demonstrated that TANs rely on increased glucose metabolism to survive in the TME and differentiate into tumor-promoting SiglecF + cells (Ancey et al, 2021 a).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, an increasing number of studies have focused on the clinical therapeutic effects of ATRA and have reported its role in downregulating the proportions of MDSCs and promoting their maturation; however, no evidence has shown that ATRA can directly reprogram the cytokine expression profiles of MDSCs. The metabolic regulation of MDSCs has emerged as a critical modulator in the suppressive tumor environment ( 42 ). ATRA can regulate amino acid and fatty acid metabolism ( 43 ).…”
Section: Discussionmentioning
confidence: 99%